The Consequences of Unilateral Withdrawals from the Paris Agreement - Mario Larch; Joschka Wanner (Center for Economic Studies and ifo Institute (CESifo), 2019)
We develop a multi-sector structural trade model with emissions from production and a con- stant elasticity of fossil fuel supply function to simulate the consequences of unilateral withdrawals from the Paris Agreement. Taking into account both direct and leakage effects, we find that a US withdrawal would eliminate a third of the world emissions reduction (25.7% direct effect and 7% leakage effect), while a potential Chinese withdrawal lowers the world emission reduction by 19.4% (8.2% direct effect and 11.2% leakage effect). The substantial leakage is primarily driven by technique effects induced by falling international fossil fuel prices.
Keywords: F14; F18; Q56; 330; climate change; international trade; carbon leakage; fossil fuel supply